Gobierno local, ciudad y política urbana - Brugué, Quim; Gomà, Ricard (El Colegio de México A.C., 1998)
This article proposes a conceptual renewal within urban politics, from the viewpoint of political sciences. The authors first review the main theoretical contributions of social sciences to urban issues, arguing that after a stage of ecological and cultural developments, urban analysis entered one of theoretical involution and empirical overfragmentation, which only the proposals of the Paris Urban School, in the late seventies, and of its British followers, in the eighties, could overcome. Second, they propose, based on the critiques of the new theorization, a reconstruction of urban politics on two foundations: a) the definition of an urban system as the array of social relations around the generation, use distribution, and social allocation of land and real estate, and b) its relation with the state level through the urban dimension of the Welfare State public policies. Finally, the authors explore the new potential of urban policies in a context of evers-tronger local governments and of the transformation of cities towards a diffuse postindustrial model.